Pigs - Munsch, Robert N., 1945-; Martchenko, Michael (Toronto : Annick Press, 1990)
The pigs make trouble as they travel from Megan's house to her school after she leaves the pigpen gate open.
450
Keywords: Pigs -- Fiction; Pigs -- Fiction